Postural Hand Synergies during Environmental Constraint Exploitation - Della Santina, Cosimo; Bianchi, Matteo; Averta, Giuseppe; Ciotti, Simone; Arapi, Visar; Fani, Simone; Battaglia, Edoardo; Catalano, Manuel Giuseppe; Santello, Marco; Bicchi, Antonio (Frontiers in Neurorobotics, 2017)
Humans are able to intuitively exploit the object shape and environmental constraints to drive the hand in order to achieve stable grasps and perform dexterous manipulations. Despite the vast range of kinematic strategies employed by humans, in this work we consider and test the hypothesis that such ability can be described in terms of a synergistic behavior in the generation of hand postures, i.e. using a reduced set of commonly used kinematic patterns. To do that we performed experiments on six subjects, who were asked to grasp objects from a flat surface. We selected objects to encourage the purposeful exploitation of the surface. We quantitatively characterized hand posture behaviour from a kinematic perspective, i.e. providing hand joint angle reconstruction in both pre-shaping and during the interaction with the environment. To determine the role of tactile feedback, we repeated the same experiment but with subjects wearing a rigid shell on the fingertips to reduce cutaneous afferent inputs that would have been generated by direct contact between the fingerpad and the environment. Results show the persistence of a set of postural synergies among all the considered conditions, supporting the hypothesis. Specifically tactile impairment does not alter the first two synergies, while contact with the environment generates a change only for higher order synergies. A good match also arises between the first synergy found in our analysis and the first synergy of grasping as quantified by previous work. Implications for robotics of our findings are finally discussed.